2017
DOI: 10.1080/02786826.2017.1368444
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the long-term effects of LII on soot and bath gas

Abstract: A combination of high-repetition rate imaging, laser extinction measurements, two-color soot pyrometry imaging, and high-resolution transmission electron microscopy of thermophoretically sampled soot is used to investigate the long-term and permanent effects of rapid heating of inflame soot during laser-induced incandescence (LII). Experiments are carried out on a laminar nonpremixed co-annular ethylene/air flame with various laser fluences. The high-repetition rate images clearly show that the heated and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This is expected behavior, since the intensity of the photo-acoustic signal depends on the increase in sensible heat (i.e., internal energy) of the soot particles, assumed that all laser-induced heat is transferred from particle to gas. The increase in internal energy in turn is directly proportional to laser fluence, as can be seen from (4) and (5).…”
Section: Multiple Exposure Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…This is expected behavior, since the intensity of the photo-acoustic signal depends on the increase in sensible heat (i.e., internal energy) of the soot particles, assumed that all laser-induced heat is transferred from particle to gas. The increase in internal energy in turn is directly proportional to laser fluence, as can be seen from (4) and (5).…”
Section: Multiple Exposure Effectsmentioning
confidence: 88%
“…Here, E(m) is the absorption function, and ex is the laser excitation wavelength. From (4) and (5), it follows that particles in the Rayleigh regime absorb laser energy at a rate proportional to their volume.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This model assumed that soot begins to anneal at temperatures as low as flame temperature, whereas experiments showed that annealing starts above 4000 K. The model suggests that annealing leads to a reduction in the absorption and emissivity characteristics of soot, whereas experiments indicated a noticeable enhancement of such optical properties once soot was annealed. One possible explanation of laser action on the optical properties of soot has been presented in [54]. Using high-speed images, they found that, at high fluence (>0.3 J/cm 2 ), a much larger region is affected than the directly heated volume.…”
Section: The Peculiarities Benefits and Future Directions Of Determimentioning
confidence: 98%
“…One should keep in mind that the LII signal lifetime at 16 bar is much shorter than the 500 ns gate (with our LII model 40 , we calculated that the LII signal from a 30 nm particle decays within less than 150 ns after the laser. We ignored the effects of bath-gas heating 41 . Thus, a 500 ns camera gate convolutes the entire LII signal.…”
Section: Svf Imaging With LIImentioning
confidence: 99%